Roseosporol A, the first isolation of a novel sesquiterpenoid from Streptomyces roseosporus. Issue 14 (18th July 2019) - Deng, Lina; Wang, Rui; Wang, Guowei; Liu, Mingxu; Liao, Zhihua; Liao, Guojian; Chen, Min
Abstract: A novel sesquiterpenoid, roseosporol A (1 ), together with 12 known compounds (2–13 ) were isolated from the ethyl acetate extract of Lsr2 -deletion mutant strain of Streptomyces roseosporus . Their structures were determined by spectroscopic methods, including NMR, HRMS, UV, IR and ECD. Abstract :